Connectivity of post‐fire runoff and sediment from nested hillslopes and watersheds. Issue 1 (30th November 2020) - Wilson, Codie; Kampf, Stephanie K.; Ryan, Sandra; Covino, Tim; MacDonald, Lee H.; Gleason, Hunter
Abstract: Wildfire increases the potential connectivity of runoff and sediment throughout watersheds due to greater bare soil, runoff and erosion as compared to pre‐fire conditions. This research examines the connectivity of post‐fire runoff and sediment from hillslopes (< 1.5 ha; n = 31) and catchments (< 1000 ha; n = 10) within two watersheds (< 1500 ha) burned by the 2012 High Park Fire in northcentral Colorado, USA. Our objectives were to: (1) identify sources and quantify magnitudes of post‐fire runoff and erosion at nested hillslopes and watersheds for two rain storms with varied duration, intensity and antecedent precipitation; and (2) assess the factors affecting the magnitude and connectivity of runoff and sediment across spatial scales for these two rain storms. The two summer storms that are the focus of this research occurred during the third summer after burning. The first storm had low intensity rainfall over 11 hours (return interval <1–2 years), whereas the second event had high intensity rainfall over 1 hour (return interval <1–10 years). The lower intensity storm was preceded by high antecedent rainfall and led to low hillslope sediment yields and channel incision at most locations, whereas the high intensity storm led to infiltration‐excess overland flow, high sediment yields, in‐stream sediment deposition and channel substrate fining. For both storms, hillslope‐to‐stream sediment delivery ratios and area‐normalised cross‐sectional channel change increased with the percent of catchment that burned at high severity. For the high intensity storm, hillslope‐to‐stream sediment delivery ratios decreased with unconfined channel length (%). The findings quantify post‐fire connectivity and sediment delivery from hillslopes and streams, and highlight how different types of storms can cause varying magnitues and spatial patterns of sediment transport and deposition from hillslopes through stream channel networks. Abstract : Low intensity rainfall led to: (1) limited hillslope‐to‐stream connectivity; and (2) channel incision at most locations. High intensity rainfall led to increased hillslope‐channel connectivity and in‐stream deposition. Unconfined channels reduced hillslope‐to‐stream connectivity during high intensity rainfall. During both rain storms, high burn severity increased hillslope‐to‐stream connectivity and cross‐sectional channel change.